CROSS-CULTURAL LITERATURE AND CULTURAL REPRODUCTION: THE CASE OF THE KOREAN AUTOBIOGRAPHY HANJUNGNOK - PARK, Kyu Hyun (International Journal of Korean Humanities and Social Sciences, 2019)
This paper is an investigation how cultural perception could be embedded in language and literature and how this helps different analyses on a same historical event. The article includes the comparison between a work of classical Korean literature, Hanjungnok (한중록), and an English-translated version of it, The Memoirs of Lady Hyekyŏng, translated by Kim-Haboush, and a work of a British novel, The Red Queen, written by Margaret Drabble. The comparison is to explore the language use regarding a perception of family relations and of gender in each version of writing. This paper concludes that authors’ and audience’s language and cultural background would influence on perceiving and analysing literature and its context so that each interpretation could be differentiated, even with the actual historical event.